ZINC PRIMING OF MAIZE SEED ENHANCES ROOTTOSHOOT Zn TRANSLOCATION BUT NOT OF ANALOGOUS HEAVY METALS - A. Kiran1; A. Wakeel; R. Ishaq; R. Mubaraka; M. Ishfaq; A. Mahmood (Journal of Animal and Plant Sciences, 2020)
Soil contaminated with heavy metals is considered a leading environmental concern as they are translocated to harvestable part of plant and ultimately influence animals and human health. Pre-germination metabolic processes stimulated by seed priming with mineral nutrient may facilitates the availability of that particular nutrient under adverse soil conditions. Seed priming with zinc (Zn) impact on Zn and heavy metals, for instance, cadmium (Cd) and nickel (Ni), uptake and their translocation within plant was evaluated in this research study. Seeds of maize were hydro-primed and Zn-primed (ZnSO4 solution) before sowing. Soil was amended with heavy metals, namely Cd and Ni and seedling was harvested after twenty days of sowing. There was no considerable treatment effect found in the various plant morphological and physiological attributes. However, interestingly, on the one hand, seed priming with Zn enhanced its uptake and distribution within plant; on the other hand, reduction in root-to-shoot translocation of Cd and Ni was observed. As a result, seed priming with Zn is not only an advantageous approach to improve Zn nutrition but also valuable to hinder the translocation of heavy metals and ultimately it can suppress inclusive deleterious impacts on human health.
Keywords: Contaminated Soils; Heavy Metals; Seed Priming; Zea mays; Zinc